45S5 Bioglass® works synergistically with siRNA to downregulate the expression of matrix metalloproteinase-9 in diabetic wounds. (June 2022) - Li, Ying; Zhang, Xin; He, Dan; Ma, Zhijie; Xue, Ke; Li, Haiyan
Abstract: Diabetic chronic wounds are difficult to heal because of the presence of excessive inflammation and high overexpression of matrix metalloproteinase-9 (MMP-9), which greatly affects the quality of life of patients with diabetes and increases the risk of death. Thus, the regulation of excessive inflammation and inhibition of MMP-9 overexpression are effective strategies to improve diabetic wound healing. The present study is the first to demonstrate that ion products of 45S5 Bioglass® (BG) can work with small interfering RNA of MMP9 (MMP9-siRNA) to reduce MMP-9 expression in tissue-forming cells and enhance the synthesis of extracellular matrix proteins (ECMs). Specifically, the BG ionic products can stimulate macrophages to convert to M2 phenotype, thereby creating a proregenerative inflammation microenvironment to indirectly suppress the expression of MMP-9 in tissue-forming cells. Chitosan nanoparticles encapsulating MMP9-siRNA (MMP9-siNP) can directly lower MMP-9 expression in tissue-forming cells. In addition, BG ionic products can promote the vascularization of endothelial cells and ECM protein synthesis by fibroblasts. Thus, injectable BG/sodium alginate (BG/SA) hydrogels loaded with MMP9-siNP can significantly accelerate the healing process of full-thickness excision wounds of diabetic rats by decreasing MMP-9 expression, improving collagen synthesis, and enhancing angiogenesis in the wounds, thereby demonstrating their great application potential in treating diabetic chronic wounds. Statement of significance: Excessive inflammation and high overexpression of MMP-9 have been considered as factors that severely hinder the healing process of diabetic chronic wounds. Effective strategies are required for the regulation of excessive inflammation and inhibition of MMP-9 overexpression to enhance diabetic wound healing. In the present work, an injectable bioglass/sodium alginate (BG/SA) hydrogel loaded with MMP9-siNP was developed; this hydrogel significantly accelerated the healing process of full-thickness excision wounds of diabetic rats by decreasing MMP-9 expression, improving collagen accumulation, and enhancing angiogenesis in the wounds. Thus, the BG/SA hydrogel loaded with MMP9-siNP has great potential for use in healing of diabetic chronic wounds. Graphical abstract: Image, graphical abstract